TEENAGERS CULTURAL VALUES TOWARDS THEIR VERNACULAR AND INDONESIAN LANGUAGES - Anjasmara Tri Dharma; Wan Muthia Lubis; Nur Alfi Syahra (Language Literacy: Journal of Linguistics, Literature, and Language Teaching, 2018)
This research is aimed at analysing the teenagers’ cultural values towards their vernacular and Indonesian languages. The populations of this research are teenagers around Langsa, especially in old sub district of Langsa named Meurandeh village. They are boys and girls with the age range from 12 to 21 years. The data were collected using questionnaires. The research result shows that teenagers’ love and appreciation to their vernacular language have been gradually fading because their parents rarely use the vernacular language and even many have not used it in their home, and it is only few of them who still consider that it is important to keep their identity. The number of the teenagers who use it as their means of communication with one another in their area is also very low. It is also shown that they do not significantly play a role in preserving the cultures of the region since the preservation is mainly done by the old. It is clear that if the old do not preserve the culture of the region, the culture may gradually vanish. Many of the teenagers tend to use Indonesian language rather than their vernacular language in their daily communication.